Vendace populations on the life table: between-lake variation and the association between early life and mature survival and growth - Marjomäki, Timo J.; Auvinen, Heikki; Helminen, Harri; Huusko, Ari; Huuskonen, Hannu; Hyvärinen, Pekka; Jurvelius, Juha; Karels, Aarno; Sarvala, Jouko; Valkeajärvi, Pentti; Karjalainen, Juha (EDP SCIENCES S A, 2025)
The vital rates related to reproduction and survival dictate the resistance and persistence of a population under perturbations. Freshwater fishes perform high levels of phenotypic plasticity thus these rates may differ widely between populations and temporally within a population. Knowledge of their ranges enables understanding the scope of population persistence and predicting the effects of environmental stressors. Time series of vendace (Coregonus albula) catch samples from 22 lakes were applied to estimate the lake-specific average length-at-age and survival in mature age groups (mS). Assuming an age-at-maturity of 2 yr and a constant length-fecundity relationship, survival from spawning to age 1 (firstS) and 2 (premS, prematurity survival) were estimated using a life table assuming a stable state. The average length at age 2 yr (L2) varied two-fold between populations, <100 - > 200 mm, and the estimated fecundity approximately eight-fold. Also, mS varied considerably, <10-70%a(-1). L2 and mS were positively associated. The premS estimate varied similar to 30-fold among lakes, <0.01 - > 0.2% per 2 yr, being highest in populations with low L2 and fecundity combined with low mS. The range of firstS estimate was even higher, 0.01-2%. This high between-lake variability seems to occur especially after hatching during the first summer. Its level is set by the factors external to the population, e.g., the abundance of key predators. Persistence with low early life survival is possible because of the wide scope of compensation in the size- and fecundity-at-age and mS. Early life survival is expected to decrease due to climate change while the compensation has its limits, increasing the risk of local extinctions.